Analysis of school principal policies regarding limited facilities and infrastructure - Barokah, Winisuda Putri; Amalia, Nur (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This research delves into the policy analysis of the principal’s approach in dealing with the infrastructure limitations at Sumberagung 1st State Elementary School. The aim is to analyze the principal's roles and policies in overcoming the school environment's infrastructure limitations. The research method uses a qualitative approach by collecting data through in-depth interviews with the school principal, teacher, and some students. The research findings depict the strategic role of the principal in formulating policies, including resource allocation, facility maintenance, and collaborative efforts with related parties. Although implementing these policies shows positive results in overcoming the limitations of infrastructure, several challenges have been identified, such as budget limitations and coordination with external stakeholders. This research contributes to understanding the dynamics of the principal's policies in dealing with infrastructure limitations, with the hope that the results can serve as the basis for thinking about improvements and the development of more effective policies in the future.